Renk-Anlam-Mekan İlişkisi - Manav, Banu (The Turkish Online Journal of Design Art and Communication, 2015)
In interior design, at the volume scale, colour is an important design paramater. During the design process, colour is a crucial subject for space identity, space psychology and personal impressions. In case colouring process is not planned well, the final product is an unexpected situation. For this reason, colour order shall be according to the space typology and its relation to space perception shall be planned. The present paper focuses on design parameters which are effective on colour perception, colour and space psychology and the importance of colour compositions.
Keywords: Renk; Mekan; Görsel Algı; Renk Kompozisyonu; Color; Space; Visual Perception; Color Composition